2015
DOI: 10.18632/oncotarget.3899
|View full text |Cite
|
Sign up to set email alerts
|

Lemur Tyrosine Kinase 2, a novel target in prostate cancer therapy

Abstract: Progression from early forms of prostate cancer to castration-resistant disease is associated with an increase in signal transduction activity. The majority of castration-resistance cancers persist in the expression of the androgen receptor (AR), as well as androgen-dependent genes. The AR is regulated not only by it associated steroid hormone, but also by manifold regulatory and signaling molecules, including several kinases. We undertook evaluation of the role of Lemur Tyrosine Kinase 2 (LMTK2) in modulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 59 publications
(62 reference statements)
0
47
0
Order By: Relevance
“…Because neurons are terminally differentiated cells it is possible that certain noxious stimuli which cause uncontrolled proliferation in other organs result in aberrant cell cycle re-entry with degenerative changes and apoptosis in nerve cells [42][43][44][45][46][47]. The role of LMTK2 has been investigated in several malignancies, particularly in prostate cancer [48][49][50][51]. Harries et al reported reduced LMTK2 expression in prostate adenocarcinoma, compared to benign prostate hyperplasia [50].…”
Section: Discussionmentioning
confidence: 99%
“…Because neurons are terminally differentiated cells it is possible that certain noxious stimuli which cause uncontrolled proliferation in other organs result in aberrant cell cycle re-entry with degenerative changes and apoptosis in nerve cells [42][43][44][45][46][47]. The role of LMTK2 has been investigated in several malignancies, particularly in prostate cancer [48][49][50][51]. Harries et al reported reduced LMTK2 expression in prostate adenocarcinoma, compared to benign prostate hyperplasia [50].…”
Section: Discussionmentioning
confidence: 99%
“…Several kinds of research have shown that treatment failure in several tumors has been attributed to the presence of CSCs [16][17][18][19]. These cells are naturally extremely resistant to different therapeutic approaches (Fig.…”
Section: Heterogeneity Of Tumor Cells Before Treatmentmentioning
confidence: 99%
“…For example, phosphorylation of AR by CDK1 and CDK9 can regulate the transcriptional activity of AR by regulating AR expression or transactivation respectively [28, 29] . Furthermore, kinases like LMTK2 and Lyn have also been implicated in manipulating AR signaling pathways and support the progression of prostate cancer to advanced androgen-independent stages of prostate cancer [30, 31] . Understanding, detailed molecular mechanisms and the role of the various phosphorylated AR species holds the key to identifying phosphorylation sites that could serve as a potential therapeutic drug targets for patients with prostate cancer and CRPC.…”
Section: Androgen and Androgen Receptor Signalingmentioning
confidence: 99%
“…Furthermore, a comparative study of LMTK2 mRNA levels in tissue from patients prostate cancer and Benign Prostatic Hyperplasia (BPH) revealed a markedly reduced level of LMTK2 in prostate cancer patients [53] . Recently, using immunohistochemistry we demonstrated that LMTK2 protein levels are also down-regulated in human prostate cancer tissue in comparison to adjacent non-cancerous tissue or tissue from patients with BPH [31] . Furthermore, we identified AR to be a binding partner of LMTK2 in prostate cancer epithelial cells.…”
Section: Lemur Tyrosine Kinase-2mentioning
confidence: 99%